Morphology, Age and Growth of Bunni, Barbus sharpeyi Gunther, 1874 in Swab marsh, south Iraq - Mohamed, Abdul-Razak M.; Al-Noor, Sajed S.; Jassim, Watfaa A. (Iraqi Journal of Aquaculture, 2022)
Morphology, age and growth of Bunni, Barbus sharpeyi Gunther, 1874 in Swab marsh, south Iraq, was studied from December 2004 to November 2005. A total of 864 B. sharpeyi (100-533mm TL) were collected using gill nets of different mesh sizes and electrical fishing. Twenty one morphometric and seven meristic characters for the species were described in the study. The morphometric characters were calculated as numerical ratio to standard and head lengths. The indices characters associated with standard length ranged from 0.0043 of eye diameter to 1.22 of total length, and with head length ranged from 0.178 of eye diameter to 0.752 of head width. The slopes of the regression lines ranged from 0.023 of eye diameter to 1.142 of total length. Fishes of 200-360mm length groups of B. sharpeyi were dominants in the samples. Total length–weight relationship of B. sharpeyi was W= 3.839 × 10-6 L 3.2017. The mean relation condition factor was 1.001. The annuli on scales formed during December and the growth of the scales was high during the period from February to August and was associated with water temperatures. The relation between standard length (L) and scale radius (S) was: L = 17.737 + 5.0469 S. The age composition ranged from 1 to 7. The standard lengths for these ages were 138.0, 202.0, 248.0, 304.8, 353.8, 393.1 and 439.2mm respectively. The growth of B. sharpeyi in Swab marsh was better than that of at Iraqi waters with the exception of B. sharpeyi at Hammar marsh. The mathematical model of growth as calculated by von Bertalanffy equation was Lt = 650 [1-e -0.138 (t + 0.642)].